INTRAABDOMINAL RETROPERITONEAL MALIGNANT FIBROUS HISTIOCYTOMA - JITGASAMESUK, Sompo; PEKANAN, Patchrin; KRAIPHIBUL, Puangtong (The ASEAN Journal of Radiology, 2023)
The malignant fibrous histiocytoma (MFH), a tumor also referred to as malignant fibrous xanthoma and fibroxanthosarcoma is a predominantly pleomorphic sarcoma usually occurring in the deep soft tissue of adults (1,2). This type of tumor also affects the bones (3). Most reports to date concern the soft tissues of the extremities; only 16% of the cases concern the abdominal cavity, where the retroperitoneum represents the most frequent site (1,4). Because of its highly variable morphologic pattern, this tumor has often been confused with other sarcomas such as pleomorphic rhabdomyosarcoma and liposarcoma. This is the case report of MFH demonstrated by IVP, Barium bowel study, ultra- sonography, CT scan and angiography